2017
DOI: 10.1128/aem.02149-16
|View full text |Cite
|
Sign up to set email alerts
|

Human Oral Buccal Microbiomes Are Associated with Farmworker Status and Azinphos-Methyl Agricultural Pesticide Exposure

Abstract: In a longitudinal agricultural community cohort sampling of 65 adult farmworkers and 52 adult nonfarmworkers, we investigated agricultural pesticide exposure-associated changes in the oral buccal microbiota. We found a seasonally persistent association between the detected blood concentration of the insecticide azinphos-methyl and the taxonomic composition of the buccal swab oral microbiome. Blood and buccal samples were collected concurrently from individual subjects in two seasons, spring/summer 2005 and win… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 111 publications
0
28
0
Order By: Relevance
“…In particular, we focused on a timepoint prior to the AZM phase-out (2005) and near the end of the phase-out (2011) to assess how substitutions away from AZM affected the overall neurodevelopmental pesticide exposome. This approach of using pesticide levels in household dust as an indicator of child pesticide exposure is supported by dust correlations of urinary biomarkers and dust pesticide levels in previous work published on this cohort [28][29][30]. Furthermore, there is strong evidence that changes in the use of agricultural pesticides is reflected in the household dust of farmworker households [31].…”
Section: Using a Neurodevelopmental Exposome Framework To Characterizmentioning
confidence: 61%
“…In particular, we focused on a timepoint prior to the AZM phase-out (2005) and near the end of the phase-out (2011) to assess how substitutions away from AZM affected the overall neurodevelopmental pesticide exposome. This approach of using pesticide levels in household dust as an indicator of child pesticide exposure is supported by dust correlations of urinary biomarkers and dust pesticide levels in previous work published on this cohort [28][29][30]. Furthermore, there is strong evidence that changes in the use of agricultural pesticides is reflected in the household dust of farmworker households [31].…”
Section: Using a Neurodevelopmental Exposome Framework To Characterizmentioning
confidence: 61%
“…The results showed that workers exposed to azinfos-methyl had a decrease in common genera found in the human oral microbiome (Streptococcus, Micrococcineae, Gemella, Haemophilus, Halomonas, Actinomycineae, and Granulicatella). Although more studies are needed to confirm the results of Stanaway et al (2017) [84], the data obtained indicate that the oral microbiome could be used as a simple biomarker for assessing pesticide exposure in epidemiological studies.…”
Section: Pesticidesmentioning
confidence: 92%
“…Finally, an epidemiological study in humans carried out by Stanaway et al (2017) [84] found that exposure to agricultural pesticides can cause dysbiosis of the human oral microbiota. A cohort of 65 agricultural workers and 52 non-agricultural workers was studied.…”
Section: Pesticidesmentioning
confidence: 99%
“…Pesticides comprise a wide range of chemicals of different classes used to ensure higher crop yields, but on the other hand, many adverse effects have been detected in animals and humans after acute or chronic exposure to pesticides, including cancer [ 1 , 2 ], lower fertility [ 3 , 4 ], metabolic changes [ 5 , 6 ] and changes in gastrointestinal microbiomes [ 7 , 8 ]. Symbiotic microorganisms play crucial roles in many important processes, such as vitamin synthesis [ 9 ], energy metabolism [ 10 ], neurodevelopment [ 11 ] and immune system modulation [ 12 ].…”
Section: Introductionmentioning
confidence: 99%